Advanced and conventional molecular techniques in the diagnosis of Mycoplasma pneumoniae in patients with respiratory tract infection - Hassan, Muntaha M.; Al-Ouqaili, Mushtak T.S.; Mohammed, Nidhal A.; Mohammed, Omar A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background:-M. pneumoniae is an important human pathogen that produces community-acquired respiratory tract infection. Diagnosis of M. pneumoniae infection is challenging and crucial for the timely initiation of the effective antibiotic therapy. Objective: This study has been undertaken to detect M. pneumoniae in respiratory samples (throat swabs, throat wash and sputum) in patients with respiratory tract infection qualitatively by conventional polymerase chain reaction (PCR). Also, more advanced one, real time PCR was used to determine mycoplasmal target gene qualitatively and quantitatively. Patients and methods: The study was performed on Seventy-five patients and thirty healthy subject as control. Genomic DNA was extracted and M. pneumoniae target gene (lipoprotein gene) was amplified using conventional PCR. Negative, positive controls and internal controls were involved in each experimental run. The amplified products were analyzed in 2% agarose gel and visualized using Red safe staining. In real time PCR, specific primer and probe mix depending on TaqMan® principle was used to detect P1 adhesion gene through FAM channel. A fluorogenic probe was included in the same reaction mixture which consists of a DNA probe labeled with a 5`-dye and a 3`-quencher. During PCR amplification Data were analyzed using Smart-cycler software and M. pneumoniae DNA copy number was estimated from the cross point threshold relative to positive standard. Results: Thirty five patients(45.5%) were positive by PCR and Thirty two (42.6 %) were positive by Real-time PCR. The highest rate of infection by using tow molecular methods were of less than 20 years of age. The quantity of M. pneumoniae DNA target gene in positive Real-time PCR were ranged between 10-2000copies/μl. Conclusion: The study concluded that both of molecular techniques conventional and real-time PCR are a rapid, reliable and ideal in diagnosis of M. pneumoniae using throat swabs, throat wash and sputum samples.